Melittin ameliorates schistosomiasis-induced liver fibrosis by suppressing signal transducer and activator of transcription 3 and nuclear factor kappa B - Ola I. Rozik; Manal M. Hussein; Ahmed S. El-elebiarie; Soad Nady (Journal of the Arab Society for Medical Research)
Background/aim Liver fibrosis is a persistent inflammatory liver disorder that contributes to a wide variety of conditions, including schistosomiasis. There is no approved therapy for liver fibrosis to date; therefore, finding effective therapeutic targets is a crucial need. There are several studies on natural products, such as bee venom and its bioactive substances like melittin (MEL), for the treatment of inflammatory disorders. The therapeutic effect of MEL in a BALB/c mouse model of Schistosoma mansoni-induced liver fibrosis was studied in this research. Materials and methods Forty-eight male BALB/c mice were classified into six groups (eight mice each): a healthy control group and five groups infected subcutaneously with cercariae of S. mansoni. The infected groups were classified into the infected control group, the Praziquantel (PZQ)-treated group, and three MEL-treated groups that received three different doses (0.1, 0.2, and 0.3 mg/kg, respectively) for 14 days. Hepatic granuloma index (GI) was measured in each experimental mouse, and serum tumor necrosis factor-α (TNF-α), interleukin-17 (IL-17), interleukin-10 (IL-10), and immunoglobulin E were measured by ELISA techniques. Additionally, expressions of signal transducer and activator of transcription 3 (STAT3) and nuclear factor kappa B (NF-κB) were assessed in splenocytes. Moreover, histopathology of the liver and spleen were also investigated. Results S. mansoni-infected mice showed significant (P<0.05) increases in the pro-inflammatory mediators and upregulate expression of STAT3, and NF-κB compared with the healthy group. MEL exhibited potent anti-inflammatory effects, as evidenced by significant (P<0.05) inhibition of the elevated pro-inflammatory cytokines, including TNF-α and IL-17, as well as immunoglobulin E levels and hepatic GI, while the anti-inflammatory IL-10 was significantly (P<0.05) increased. In addition, MEL treatment significantly (P<0.05) inhibited the expression of STAT3 and NF-κB in splenocytes compared with healthy mice. The most positive effects were associated with MEL were observed at the maximum dose. Conclusion According to the findings of this study, MEL alleviates the degree of hepatic inflammation in a mouse model of S. mansoni-induced liver fibrosis by modulating inflammation through suppression of STAT3 and NF-κB.